A Simple In-Season Bioassay for Detecting Glyphosate Resistance in Grass and Broadleaf Weeds Prior to Herbicide Application in the Field. Issue 4 (December 2014) - Kaundun, Shiv S.; Hutchings, Sarah-Jane; Harris, Suzanne C.; Jackson, Lucy V.; Shashi-Kiran, Rekha; Dale, Richard P.; McIndoe, Eddie
Abstract : The implementation of a successful glyphosate resistance management strategy requires a simple and cost-effective method for detecting resistance in key weeds. To date, however, glyphosate resistance is still routinely confirmed via laborious and time consuming whole-plant pot assays using seeds collected at the end of the growing season. Here, we describe a simple, early-season bioassay for detecting evolved glyphosate resistance in grass and broadleaf weeds. It involves transplanting suspected glyphosate resistant seedlings alongside known sensitive and resistant standards into agar containing informative rates of herbicide and recording percentage survival 14 d after plating. The method was validated using sensitive and resistant populations of Lolium, Eleusine, Conyza, and Amaranthus species encompassing the main glyphosate resistance mechanisms, namely, impaired translocation, EPSPS gene duplication, and mutations. The whole plant pot and agar-based seedling tests generated comparable resistance indices in dose-response assays and percentage survival at discriminating glyphosate rates. The method was applied successfully to detect resistance in a rigid ryegrass population collected from a French vineyard well before glyphosate was applied in the field for the current season. Additionally, the test was shown to be highly transferable to several other grass and broadleaf weeds that have evolved resistance to glyphosate. One major attribute of the method is that it is capable of detecting resistance regardless of the mechanism involved. In addition to being very simple, quick and, cost-effective, it allows determination of glyphosate resistance in weeds prior to field application. It thus offers the opportunity for an informed choice of herbicides for effective weed control.